2021 Sixth International Conference on Informatics and Computing (ICIC) 2021
DOI: 10.1109/icic54025.2021.9632995
|View full text |Cite
|
Sign up to set email alerts
|

Extending ECM with Quality Factors to Investigate Continuance Intention to Use E-learning

Abstract: This paper has purpose to investigate the impact of quality factors on satisfaction and continuing intention in using e-learning system. The study employs expectationconfirmation model (ECM) to express the effect of Information Quality, System Quality, Service Quality on Confirmation and Satisfaction and adds Perceived Usefulness and Self efficacy to reveal their effect on Satisfaction. The proposed model was tested using 325 respondents. They are young people that live in digital native culture. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Task technology fit also has positive effect on Satisfaction [9] and perceived usefulness [8]. Therefore, we proposed: H2: Task technology fit has positive effect on perceived usefulness H3: Task technology fit has positive effect on confirmation H4: Task technology fit has positive effect on satisfaction Self-Efficacy -> Satisfaction Self-efficacy is the satisfied of student in accessing academic content of MOOCs by using computers [3]. Several research conducted studies on e-learning and stated that self-efficacy has direct effect on satisfaction [3], [10], [11], [7].…”
Section: Task Technology Fit On Perceived Usefulness Confirmation And...mentioning
confidence: 99%
See 4 more Smart Citations
“…Task technology fit also has positive effect on Satisfaction [9] and perceived usefulness [8]. Therefore, we proposed: H2: Task technology fit has positive effect on perceived usefulness H3: Task technology fit has positive effect on confirmation H4: Task technology fit has positive effect on satisfaction Self-Efficacy -> Satisfaction Self-efficacy is the satisfied of student in accessing academic content of MOOCs by using computers [3]. Several research conducted studies on e-learning and stated that self-efficacy has direct effect on satisfaction [3], [10], [11], [7].…”
Section: Task Technology Fit On Perceived Usefulness Confirmation And...mentioning
confidence: 99%
“…Adapted from [12], Satisfaction was defined as "the end user's affective attitude towards a MOOCs application. Several studies showed the significantly effect of Confirmation on Satisfaction [2], [3], [4], [5], [6], [7]). Khaled [2] and Day [4] conducted research on user acceptance of MOOCs, Prasetya [3], Prasetya [5], and Widiantoro [7] examine the adoption of eLearning systems on young people, and Prasetya [6] studied on consumer acceptance on e-marketplace.…”
Section: Confirmation On Satisfaction and Perceived Usefulnessmentioning
confidence: 99%
See 3 more Smart Citations